The role of oxidative stress and inflammatory response in the pathogenesis of mastitis in dairy cows - Romana Turk; Matea Koledić; Nino Maćešić; Miroslav Benić; Vesna Dobranić; Dražen Đuričić; Luka Cvetnić; Marko Samardžija (Mljekarstvo)
Mastitis is one of the most frequent diseases of dairy cows throughout the world, therefore it causes the greatest economic losses in dairy cattle industry. These losses are reflected through: reduced milk production, increased costs of medication and the other animal health services, reduced fertility, early culling of animals and the value of discarded milk. Mastitis is also important from the aspects of public health, milk processing and animal welfare. In the pathogenesis of mastitis the key role plays the innate immune response which is the first line of defence against the pathogen invasion of the udder. The innate immune response generates an inflammatory reaction which is the elementary response of an organism to the tissue trauma induced by any physical, chemical or biological causative agent, but primarily it is the protective mechanism of a vital significance which includes increased phagocytic activity, secretion of antimicrobial substances, fibrosis as well as the alterations in tissue structure of affected organ or body cavity. The release of a number of inflammatory mediators as well as reactive oxygen species (ROS) is an important part of inflammatory response. In dairy cows, the metabolic challenge that occurred during the transition from dry period to early lactation may additionally increase the release of ROS which may contribute to development of oxidative stress and inflammatory response. Oxidative stress is defined as a shift in the balance from cellular oxidation-reduction reactions towards oxidation, i.e. to the state of excessive release of oxidants when their removal by antioxidants is impaired and even insufficient. During peripartum period antioxidantive status of dairy cows is seriously impaired and consequently both the oxidative stress and inflammatory response may present the predisposing factors to their higher susceptibility to intramammary infections (IMI) and mastitis. This association between oxidative stress and inflammation during IMI and mastitis indicates their role in the pathogenesis of mastitis. Thus, a better understanding of such a synergism could contribute to development of new approaches to prevention and therapy of IMI and mastitis.